Diffuse advanced hepatocellular carcinoma after HCV eradication in an HIV-infected patient: A unique complete response to sorafenib - Nunes, Gonçalo; Fonseca, Cristina; Patita, Marta; Aleixo, Mario João; Ramalho, Miguel; Fonseca, Jorge (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Nunes G, Fonseca C, Patita M, Aleixo MJ, Ramalho M, Fonseca J. Diffuse advanced hepatocellular carcinoma after HCV eradication in an HIV-infected patient: A unique complete response to sorafenib. Turk J Gastroenterol 2020; 31(2): 184-6.